Estimating the Cost of Early Infant Male Circumcision in Zimbabwe: Results From a Randomized Noninferiority Trial of AccuCirc Device Versus Mogen Clamp. (15th August 2015) - Mangenah, Collin; Mavhu, Webster; Hatzold, Karin; Biddle, Andrea K.; Madidi, Ngonidzashe; Ncube, Getrude; Mugurungi, Owen; Ticklay, Ismail; Cowan, Frances M.; Thirumurthy, Harsha
Abstract : Background: Safe and cost-effective programs for implementing early infant male circumcision (EIMC) in Africa need to be piloted. We present results on a relative cost analysis within a randomized noninferiority trial of EIMC comparing the AccuCirc device with Mogen clamp in Zimbabwe. Methods: Between January and June 2013, male infants who met inclusion criteria were randomized to EIMC through either AccuCirc or Mogen clamp conducted by a doctor, using a 2:1 allocation ratio. We evaluated the overall unit cost plus the key cost drivers of EIMC using both AccuCirc and Mogen clamp. Direct costs included consumable and nonconsumable supplies, device, personnel, associated staff training, and environmental costs. Indirect costs comprised capital and support personnel costs. In 1-way sensitivity analyses, we assessed potential changes in unit costs due to variations in main parameters, one at a time, holding all other values constant. Results: The unit costs of EIMC using AccuCirc and Mogen clamp were $49.53 and $55.93, respectively. Key cost drivers were consumable supplies, capacity utilization, personnel costs, and device price. Unit prices are likely to be lowest at full capacity utilization and increase as capacity utilization decreases. Unit prices also fall with lower personnel salaries and increase with higher device prices. Conclusions: EIMC has a lower unit cost when using AccuCirc compared with Mogen clamp. To minimize unit costs, countries planning to scale-up EIMC using AccuCirc need to control costs of consumables and personnel. There is also need to negotiate a reasonable device price and maximize capacity utilization.